2015
DOI: 10.1038/ngeo2539
|View full text |Cite
|
Sign up to set email alerts
|

Coastal vulnerability across the Pacific dominated by El Niño/Southern Oscillation

Abstract: To predict future coastal hazards, it is important to quantify any links between climate drivers and spatial patterns of coastal change. However, most studies of future coastal vulnerability do not account for the dynamic components of coastal water levels during storms, notably wave-driven processes, storm surges and seasonal water level anomalies, although these components can add metres to water levels during extreme events. Here we synthesize multi-decadal, co-located data assimilated between 1979 and 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
238
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 322 publications
(250 citation statements)
references
References 34 publications
9
238
1
2
Order By: Relevance
“…El Niño conditions are also generally associated with a strengthening of the Aleutian low and of high pressures west of the Rocky Mountains [Philander, 1983;Barnard et al, 2015]. This enforces the winds over north-western Canada and Alaska, explaining why the long-term increase of ENSO is correlated with the growth of extreme WEF along the north-eastern Pacific coasts (Figures 4t and 4u).…”
Section: 1002/2016gl072488mentioning
confidence: 96%
See 2 more Smart Citations
“…El Niño conditions are also generally associated with a strengthening of the Aleutian low and of high pressures west of the Rocky Mountains [Philander, 1983;Barnard et al, 2015]. This enforces the winds over north-western Canada and Alaska, explaining why the long-term increase of ENSO is correlated with the growth of extreme WEF along the north-eastern Pacific coasts (Figures 4t and 4u).…”
Section: 1002/2016gl072488mentioning
confidence: 96%
“…In the north-western Pacific, a progressive shift southward of the jet stream and of the storm-tracks under El Niño conditions results in a colder and more stable climate [Wang et al, 2000;Barnard et al, 2015], exemplified by strong negative correlation between the trends in extreme WEF and the ENSO index (ρ ¼ À0:95). A rather strong negative correlation is also observed for the northern tropical Atlantic (ρ ¼ À0:91; Figures 4v and 4w).…”
Section: 1002/2016gl072488mentioning
confidence: 99%
See 1 more Smart Citation
“…During extreme events, the energetic atmospheric conditions result in transfer of mass and energy in the water element, which through the interaction with the bathymetry are manifested as increased water levels. When the latter coincide with spring tides, they can lead to extreme events, affecting landward areas which are normally protected by water (Barnard et al, 2015;Bertin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The IPO also appears to modulate the frequency of El Niño events, whereby the occurrence of El Niño events is shown to be significantly elevated during the positive phase, with the last 350 years showing that the frequency of La Niña is significantly higher during negative IPO phases [6]. Reference [11] reported that for recent decades , coastal vulnerability across the Pacific correlates with ENSO. The combination of IPO and ENSO provides the broad framework for understanding Australian climate episodic behaviour.…”
Section: Introductionmentioning
confidence: 99%